1997
DOI: 10.1079/bjn19970069
|View full text |Cite
|
Sign up to set email alerts
|

Low-sodium diet in pregnancy: effects on blood pressure and maternal nutritional status

Abstract: In ninety-four Dutch nulliparous women the effects of a low-Na diet in pregnancy on blood pressure, energy and nutrient intake, Ca metabolism, Zn and Mg status and body composition were studied longitudinally. The women were randomly divided into an intervention group (n 41), which used a low-Na diet (mean urinary Na excretion 61 mmoV24 h) from week 14 of pregnancy until delivery and a control group (n 53; mean urinary Na excretion 142 mmoV24 h). No effect of the diet on blood pressure was observed. The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…In five of the studies in Table 3 (26,27,31,34,36), reported EI was considerably lower than expected EI (ranging from -15% to -37%). In the study by Antal et al (3), reported EI differed by +10%, +1%, -9%, and -12% from expected EI in gestational week 12, 20, 30, and 38, respectively.…”
Section: Figurecontrasting
confidence: 51%
See 1 more Smart Citation
“…In five of the studies in Table 3 (26,27,31,34,36), reported EI was considerably lower than expected EI (ranging from -15% to -37%). In the study by Antal et al (3), reported EI differed by +10%, +1%, -9%, and -12% from expected EI in gestational week 12, 20, 30, and 38, respectively.…”
Section: Figurecontrasting
confidence: 51%
“…Studies were included if they (a) were published on MEDLINE (http://www.ncbi.nlm.nih.gov/ entrez/query.fcgi) before September 2006; (b) reported original data; (c) were identified by the search terms "EI" and "pregnant women" or "human pregnancy"; (d ) were written in English; (e) reported an average EI, a mean body weight no later than gestational week 14, and a mean gestational weight gain of 12-14 kg and/or an average birth weight around 3.5 kg; and ( f ) were conducted in developed countries. Seven studies meeting these criteria were identified (3,22,26,27,31,34,36). Table 3 describes subject characteristics, dietary assessment methods, gestational weeks when diet was assessed, prepregnancy body weight, and reported mean EI for the seven studies.…”
Section: Figurementioning
confidence: 99%
“…After full text assessment, two studies were excluded because they lacked a control group 16,17 . One study was excluded because it focused on the effects on blood pressure of a low‐sodium diet in pregnancy 18 …”
Section: Resultsmentioning
confidence: 99%
“…Although salt is a widely used and effective traditional preservative and flavour enhancer, high sodium intakes can also bring health risks (Goulding 1997; Law 1997; Van der Maten et al. 1997).…”
Section: Introductionmentioning
confidence: 99%